(untitled) (LEARNing Landscapes, 2019)
This study explored voices of early learning teachers engaged in discussions in an online outdoor play and nature pedagogy course. Three core questions were investigated that focused on early learning teachers’ perceptions and practices of children’s access to quality outdoor play and nature experiences. The results support previous research that indicated that teachers’ perceptions, experiences, values, knowledge, and attitudes influence children’s outdoor play experiences. The findings suggest the need to increase access to professional learning that contributes to early learning teachers enhancing their confidence, awareness, and intentional programming, which results in shifting attitudes to fully embrace outdoor play and pedagogy.